Unusual Case of Giant Multicystic Acanthomatous Ameloblastoma of Mandible in a 70 years old Male - Singh, Prem; Garg, Monika; Nauhria, Samal; Gupta, Sonam (Asian Journal of Medical Sciences, 2013)
Asian Journal of Medical Science, Volume-4 (2013), Pages 1-2 DOI: http://dx.doi.org/10.3126/ajms.v4i4.7847